Financial Behavior: Menilai Peran Literasi Keuangan Dan Penggunaan E-Wallet Pada Mahasiswa - Dimas Anggia; Taufik Sadikin; Ahmad Johan (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The rapid development of digital financial technology has significantly transformed consumption behavior, particularly among university students as a highly adaptive group to technological advancements. The emergence of e-wallets, supported by transactional convenience and promotional incentives, has the potential to increase consumptive behavior, while financial literacy is theoretically expected to act as a control mechanism. However, the inconsistency between financial knowledge and actual behavior indicates a behavioral gap that requires further investigation. This study aims to examine the effect of financial literacy and e-wallet usage on students’ consumptive behavior. A quantitative approach with descriptive and verificative designs was employed, using questionnaire data collected from 110 respondents and analyzed through multiple linear regression. The results indicate that financial literacy is categorized as good, e-wallet usage is high, and consumptive behavior is moderately high. Partially, financial literacy does not have a significant effect, whereas e-wallet usage has a positive and significant effect on consumptive behavior. Simultaneously, both variables have a significant effect with a coefficient of determination of 19.5%. These findings highlight the dominant role of financial technology over cognitive factors and reinforce the existence of a knowledge–behavior gap.